Nocardioides panacis sp. nov., isolated from soil of a ginseng field. Issue 6 (1st June 2022) - Park, Yuna; Liu, Qingzhen; Maeng, Soohyun; Choi, Won Jung; Chang, Yoonjee; Im, Wan-Taek
Abstract : A bacterial strain designated as G188 T was isolated from ginseng field soil in the Republic of Korea. Phylogenetic analysis of 16S rRNA gene sequences showed that strain G188 T formed a distinct lineage within the genus Nocardioides, family Nocardioidaceae, order Propionibacteriales . Sequence similarity revealed that strain G188 T was most closely related to Nocardioides iriomotensis IR27-S3 T (97.7 % 16S rRNA similarity). The genome size of strain G188 T was 4 901 775 bp, and the genomic DNA G+C content was 72.3 mol%. The average nucleotide identity and DNA–DNA hybridization values with other Nocardioides species were less than 75.6 and 20.1 %, respectively. The main fatty acids of strain G188 T were C17 : 0, C17 : 1  ω 8 c and iso-C16 : 0 . The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol, and phosphatidylinositol, and the major respiratory quinone was menaquinone 8, supporting that strain G188 T was affiliated with the genus Nocardioides . Based on biochemical, chemotaxonomic and phylogenetic analyses, the novel species Nocardioides panacis G188 T (KACC 21695 T =LMG 31733 T ) is proposed.